Regulating the registration and operation of homestay in Malaysia / Rozlinda Abdullah - Abdullah, Rozlinda (2022)
The Malaysian Homestay Programme introduced and spearheaded by the Ministry of Tourism Malaysia (MOTAC) is a form of rural cultural-community-based tourism that strategically aims to eliminate poverty and economically empower disadvantaged local villagers through income diversification in the sustainable development agenda. MOTAC has provided the Malaysian Homestay Registration Guidelines (MOTAC Guidelines) to govern the Malaysian Homestay Programme, which is not comprehensive and only addresses registration, criteria, and application process procedures. Thus, to boost the confidence of tourists and maintain the sustainability of the Malaysian Homestay Programme, this research examines the shortcomings of the current MOTAC Guidelines, the Handbook on Homestay Operation, and other related laws which may directly and indirectly govern operations and registration of homestay in Malaysia, such as the Innkeepers Act 1952, Uniform Building By-Laws Act 1984, National Land Code 1950, Town and Country Planning Act and also Hotel (Malacca) By-Laws and consequently propose some improvements. A comparative study (when necessary) is made with other similar legal instruments applied by other selected countries in identifying the strength and weaknesses in the operation and registration of homestay in Malaysia, such as Rules of Homestay Facilities 2001 in Taiwan, ASEAN Homestay Standard, and the UK and USA related law for benchmarking and lessons to be learned. An analysis of the homestay programme from the Islamic perspective is also being made. By adopting a qualitative method, this research recommends that the best model of homestay should be adopted by categorising the homestay into different types of homestays i.e., home-sharing, temporary short-term rentals, and short-term commercial rentals, in order to establish and differentiate the related legal requirements, for example, planning permission. Hence, if the homestay operator has not changed the nature of the purpose of the property, planning permission is not needed. However, planning permission is required to be obtained if there is a change of use from private residential property to homestay services that has been commercialised to a certain extent represents a material change of use of the property. This research also recommends that the Local Planning Authority may consider issuing homestay operators provisional or temporary planning permission (TPP), which is a short-term approval and only permissible for a transitory nature of the use of land and buildings. In addition, MOTAC Guidelines need to improve on matters relating to pre- and post registration, including the requirement to include provisions on disclosure of applicants' income, safekeeping of guests' particulars, distribution of guests, the safety of guest's property, and Syariah principles in the homestay code of conduct. This research is significant in assisting the policymakers in regulating the registration and operation of Malaysian Homestay Programme in order to maintain its sustainability.